Konstantin Ustinovich Chernenko as the Leader of the CPSU and the Soviet Union (1984—1985) - M. F. Polynov (Научный диалог)
The activity of Konstantin Ustinovich Chernenko as the General Secretary of the Central Committee of the CPSU is analyzed. The author reveals the objective and subjective factors that influenced his coming to power. The relevance of the study is due to the need to obtain objective knowledge and understanding of the content of Chernenko’s internal policy at the highest post in the party. The novelty of the research lies in the fact that, based on an analysis of various historical sources, the question of which areas of the CPSU policy was focused on Chernenko’s attention as General Secretary for 13 months. It is stated that Chernenko left a noticeable mark on politics, despite the fact that he was unable to propose a policy that could be identified with his name and defined as “Chernenko’s policy”. It has been proved that he, on the whole, continued the policy pursued by Andropov, and did not seek to “freeze” the ongoing reforms. It is shown that he had a clear understanding of the need to reform not only the economy, but also some spheres of society, especially education. It is emphasized that he also raised the issue of the need to enhance the role of the Soviets. It is shown that in the top leadership of the USSR  Chernenko was perceived as a temporary leader, which exacerbated the struggle for power within the Politburo.